The Effect of Emotional Intelligence and Work Motivation on the Professional Competence of Elementary School Teachers in Mapanget District, Manado City - Agnes M. Goni; Emelinda Kumolontang (International Journal on Integrated Education, 2022)
This study aims to analyze and examine the effect of emotional intelligence and work motivation on the professional competence of teachers. The research was conducted in elementary schools in Mapanget District, Manado City as many as 20 schools with the number of respondents as the research sample as many as 89. The sampling technique used was simple random sampling technique. Testing the validity of the instrument using the Pearson Product Moment formula and testing the reliability of the instrument using the Alpha method. The research hypotheses were tested using simple linear regression analysis techniques and multiple linear regression. Testing the requirements of the regression analysis carried out normality test and linearity test. Based on the results of the study it was found that:️=24,231 + 0.887X1;(2) there is a significant influence of teacher work motivation on the professional competence of elementary school teachers in Mapanget District, Manado City by 48.3%, while the level of professional competence of teachers can be predicted by the regression equation:=53,539 + 0.619X2; (3) there is a significant effect of emotional intelligence and work motivation of teachers together on the professional competence of elementary school teachers in Mapanget District, Manado City by 54.7%, while the level of professional competence of teachers can be predicted by the regression equation:=23,893 + 0.473X1+ 0.396 X2.This study suggests that to improve the professional competence of elementary school teachers in Mapanget District, Manado City, it is necessary to increase emotional intelligence and increase teacher work motivation.